2 1 + 4 × 2 3 + 6 × 4 × 2 5 + 8 × 6 × 4 × 2 7 + ⋯ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same as mine method
how did you do the partial fractions?
That's wrong.You haven't chosen the right nth term.
That's not the correct answer!
Log in to reply
Sorry, the answer is perfect!
Observation of this sum tells us all numerators are odd. Wasn't that written as 2 k − 1 ? It actually is and the denominators are all products of consecutive even numbers which seems to be the same as ( 2 k ) ! ! , where the double exclamation mark stands for ‘double factorial’ or ‘semifactorial’ and can be rewritten as a single factorial. So now let us rewrite the different terms.
S = 1 ⋅ 2 2 ⋅ 1 − 1 + 2 ⋅ 2 ⋅ 1 ⋅ 2 2 ⋅ 2 − 1 + 3 ⋅ 2 ⋅ 2 ⋅ 2 ⋅ 1 ⋅ 2 2 ⋅ 3 − 1 + 4 ⋅ 2 ⋅ 3 ⋅ 2 ⋅ 2 ⋅ 2 ⋅ 1 ⋅ 2 ) 2 ⋅ 4 − 1 + … = k = 1 ∑ ∞ 2 k k ! 2 k − 1 = k = 1 ∑ ∞ 2 k k ! 2 k ⋅ k − 1 k − 1 − 2 k k ! 1 = k = 1 ∑ ∞ 2 k ( k − 1 ) ! 2 − 2 k k ! 1 = k = 1 ∑ ∞ 2 k − 1 ( k − 1 ) ! 1 − 2 k k ! 1 (‘telescoping sum’: most terms will cancel out) = 1 1 − 2 1 + 2 1 − 8 1 + 8 1 − 4 8 1 + 4 8 1 − 3 8 4 1 + 3 8 4 1 − + … − ∞ 1 = 1 − 0 = 1
Just for the sake of diversity, a solution with Taylor's series:
re-write the original problem
2 1 + 4 × 2 3 + 6 × 4 × 2 5 + ⋯ = 2 1 + 2 2 ⋅ 2 ! 3 + 2 3 ⋅ 3 ! 5 + ⋯
We know that
e x 2 − 1 = x 2 + 2 ! x 4 + 3 ! x 6 + ⋯
x e x 2 − 1 = x + 2 ! x 3 + 3 ! x 5 + ⋯
differentiate both sides:
x 2 ( 2 x 2 − 1 ) e x 2 + 1 = 1 + 2 ! 3 x 2 + 3 ! 5 x 4 + ⋯
2 x 2 ( 2 x 2 − 1 ) e x 2 + 1 = 2 1 + 2 ⋅ 2 ! 3 x 2 + 2 ⋅ 3 ! 5 x 4 + ⋯
now plug in x = 2 1
1 = 2 1 + 2 2 ⋅ 2 ! 3 + 2 3 ⋅ 3 ! 5 + ⋯
Use harmonic progression with telescoping series
It sums to 1 - 1/infinity where 1/infinity is 0 so answer is 1 - 0 = 1
Let S = 1/2 + 1/4 2 + 1/6 4 2 + 1/8 6 4 2 +..... =1/2 + (1/2) (1-3/4) + (1/4 2) (1-5/6) + (1/6 4 2) (1-7/8)+........ =1/2 + 1/2 + 1/4 2 + 1/6 4 2 +..... -(3/4 2 + 5/6 4 2 + 7/8 6 4 2+......) So, S=1/2 + S -(3/4 2 + 5/6 4 2 + 7/8 6 4 2+......) So, (3/4 2 + 5/6 4 2 + 7/8 6 4 2+......) = 1/2 So, ½ + 3/4 2 + 5/6 4 2 + 7/8 6 4*2+......) = ½+½=1
most simple answer:
2 1 + 4 × 2 3 + 6 × 4 × 2 5 + 8 × 6 × 4 × 2 7 + ⋯
converting the numerator to a subtraction:
2 1 + 4 × 2 4 − 1 + 6 × 4 × 2 6 − 1 + 8 × 6 × 4 × 2 8 − 1 + ⋯ (the key is see that the substraction in the numerator has the max value of the denominator and 1 xD)
splitting fractions and simplifying factors:
2 1 + ( 4 × 2 4 − 4 × 2 1 ) + ( 6 × 4 × 2 6 − 6 × 4 × 2 1 ) + ( 8 × 6 × 4 × 2 6 − 8 × 6 × 4 × 2 1 ) + ⋯
2 1 + ( 2 1 − 4 × 2 1 ) + ( 4 × 2 1 − 6 × 4 × 2 1 ) + ( 6 × 4 × 2 1 − 8 × 6 × 4 × 2 1 ) + ⋯
cancelling similar terms:
2 1 + 2 1 + 0 + 0 + 0 + ⋯ = 1
Problem Loading...
Note Loading...
Set Loading...
The n th term T n S We can easily S of the sequence is given by = 2 n n ! 2 n − 1 = n = 1 ∑ ∞ T n = n = 1 ∑ ∞ 2 n n ! 2 n − 1 = n = 1 ∑ ∞ 2 n − 1 ( n − 1 ) ! 1 − 2 n n ! 1 see that the sum telescopes, = 2 1 − 1 ( 1 − 1 ) ! 1 = 1